Bispidine-Based Macrocycles: Achievements and Perspectives - Medved’ko, Aleksei V.; Gaisen, Savelii V.; Kalinin, Mikhail A.; Vatsadze, Sergey Z. (Organics (Basel), 2023)
This review presents all currently known macroheterocyclic compounds that include a bispidine (3,7-diazabicyclo[3.3.1]nonane) fragment in their structure. A classification of bispidine-containing macroheterocycles, which is based on the ring size and the nature of bispidinic nitrogen atoms, is suggested. Synthetic approaches to the studied compounds are classified and considered. The features of the crystal structures and solution behavior of bispidine macroheterocycles are analyzed. Prospects for the development of these organic receptors are proposed.